Aplicación de sanciones de tercera velocidad para los que infringen el deber objetivo de cuidado de los ciclistas - Villavicencio Muñoz, Tatiana Marianella (2022)
In the present investigation titled: APPLICATION OF THIRD-SPEED SANCTIONS FOR THOSE WHO INFRINGE THE OBJECTIVE DUTY OF CARE OF CYCLISTS. Its general objective is to legally analyze the objective duty of care in the Salinas canton of the Santa Elena province, specifically on the Punta Carnero road, studying the different doctrines that support the legal figure in question. Determining all its antecedents and evolution throughout the history of the objective duty of care in cyclists. The deductive methodology was used, among the types of research used we have: the historical, documentary, explanatory, descriptive, the approach used in this research is: mixed, qualitative and quantitative, for the techniques and instruments the interview and survey were used.